Modern Reading of the Sociology of Morality - Oksana A. Polyushkevich (Transbaikal State University, 2021)
The paper analyzes theoretical concepts and empirical tools for the study of morality, altruism, contributing to the development of ideas, beliefs and values about justice or its absence and trust or distrust in oneself, people around and social institutions. The relevance of studying this issue has become especially acute during a pandemic, when questions of morality and ethics have become urgent for many people in everyday space with the daily choice of their own behavior, the safety of themselves and others during and after a pandemic. These research focuses are studied within the framework of an interdisciplinary approach to the sociology of morality. It is shown that the moral dimension of social reality is a key marker of social reproduction. This position is proved by the appeal of contemporaries within the framework of sociology, psychology, philosophy to these topics, as well as the author’s own empirical research conducted in 2019–2020 by filling out diaries for six months (165 people), where moral emotions arising in any life were recorded situations, the methodology of Sh. Schwartz was used to identify the basic values (survey of research participants) and focus group conversations (54 people), which made it possible to identify the discrepancy between the declared values and situational reactions to various interactions mediated by moral emotions. The article traces the influence of social interaction, produced through the influence of social institutions that develop group norms, on the behavior of individuals in certain situations of interaction and group reactions in the process of communication and subsequent assessments of this process. It is proved how moral emotions either strengthen the existing functioning of social institutions or destroy it, eroding the clear framework of what is proper, acceptable, and correct. It also shows how and why situational factors influence norms and values more than general ideas about moral norms. The article may be of interest to philosophers, sociologists and specialists in helping professions for fixing and reflecting on moral states and transformations of the modern social environment.